Tailoring thermal expansion of shape memory alloys through designed reorientation deformation. (1st October 2021) - Li, Qiao; Onuki, Yusuke; Sun, Qingping
Abstract: Manipulating macroscopic linear thermal expansion (TE) through microstructure engineering is emerging as a new research topic of shape memory alloys (SMAs). Here, we perform a modelling-and-experiment combined study to design and tune the coefficient of TE (CTE) of polycrystalline martensitic SMAs based on reorientation deformation. Using Landau thermodynamic theory of first-order phase transition, we prove that the martensite lattices of most SMAs possess intrinsic negative (positive) TE along the directions of transformation elongation (contraction). As a combined result of such intrinsic lattice-level TE and the extrinsic reorientation-deformation texture, the overall linear CTEs of martensite polycrystals decrease (increase) with the amount of reorientation stretching (contraction). The deformation paths and strain magnitudes are designed to obtain zero linear TE in 17 types of bulk SMAs and are verified by the available experimental data. Furthermore, through designed cross-rolling on martensitic NiTi sheets, we obtain ultralow in-plane CTEs (+0.13 × 10 −6 K −1 ∼ +1.4 × 10 −6 K −1 ), which are smaller than the reported values of SMAs and are even smaller than the commercial FeNi Invar alloy (+2.0 × 10 −6 K −1 ). Our work provides a theoretical base to design SMAs with desired linear CTEs for many applications. Graphical abstract: Image, graphical abstract